The Neurologic Manifestations of Coronavirus Disease 2019 Pandemic: A Systemic Review - Tsai, Sheng-Ta; Lu, Ming-Kuei; San, Shao; Tsai, Chon-Haw (Frontiers in Neurology, 2020)
Objective Review and integrate the neurologic manifestations of the Coronavirus Disease 2019 (COVID-19) pandemic, to aid medical practitioners who are combating the newly derived infectious disease. Methods We reviewed the clinical research, consisting of mainly case series, on reported neurologic manifestations of COVID-19. We also reviewed basic studies to understand the mechanism of these neurologic symptoms and signs. Results We included 79 studies for qualitative synthesis and 63 studies for meta-analysis. The reported neurologic manifestations were olfactory/taste disorders (35.6%), myalgia (18.5%), headache (10.7%), acute cerebral vascular disease (8.1%), dizziness (7.9%), altered mental status (7.8%), seizure (1.5%), encephalitis, neuralgia, ataxia, Guillain-Barre syndrome, Miller Fisher syndrome, intracerebral hemorrhage, polyneuritis cranialis, and dystonic posture. Conclusions Neurologic manifestations in COVID-19 may alert physicians and medical practitioners to rule in high-risk patients. The increasing incidence of olfactory/taste disorders, myalgia, headache, and acute cerebral vascular disease renders a possibility that COVID-19 could attack the nervous system. The cytokine secretion and bloodstream circulation (viremia) are among the most possible routes into the nervous system.